Cyclic Nucleotide Signaling in Plants Methods and Protocols - Gehring, Chris; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Over the last two decades there has been a growing interest in cyclic nucleotide research in plants with an emphasis on the elucidation of the roles of cGMP and cAMP. In Cyclic Nucleotide Signaling in Plants: Methods and Protocols, expert researchers in the field detail many approaches to better understand the biological role of this important signaling system. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.     Authoritative and practical, Cyclic Nucleotide Signaling in Plants: Methods and Protocols seeks to aid scientist in further understanding signal transduction and the molecular mechanisms underlying cellular signaling.
Molecular Methods for the Study of Signal Transduction in Plants -- Recombinant Expression and Functional Testing of Candidate Adenylate Cyclase Domains -- Quantification of Cyclic Dinucleotides by Reversed-Phase LC-MS/MS -- Determination of ADP-ribosyl cyclase activity, cyclic ADP-ribose and Nicotinamide adenine dinucleotide phosphate in Tissue Extracts -- In vivo imaging of cGMP in plants -- Characterization of Heterologously Expressed Transporter Genes by Patch- and Voltage-Clamp Methods: Application to Cyclic Nucleotide-Dependent Responses -- Non-invasive Microelectrode Ion Flux Estimation Technique (MIFE) for the study of the regulation of root membrane transport by cyclic nucleotides -- Calcium imaging of the cyclic nucleotide response -- Identification and Quantification of Signal Molecule-dependent Protein Phosphorylation -- Comparative Gel-based (Phospho)proteomics in Response to Signaling Molecules -- An Affinity Pull-down Approach to Identify the Plant Cyclic Nucleotide Interactome -- Structural and Functional Characterization of Receptor Kinases with Nucleotide Cyclase Activit -- Computational Identification of Candidate Nucleotide Cyclases in Higher Plants -- Identification of Cyclic Nucleotide Gated Channels Using Regular Expressions -- Inferring biological functions of guanylyl cyclases with computational methods -- Identification and Characterization of Cyclic Nucleotide Phosphodiesterases -- Detection of reactive oxygen species down-stream of cyclic nucleotide signals in plants -- Measurement of nitric oxide in plant tissue using difluorofluorescein and oxyhaemoglobin -- Infra-red Gas Analysis (IRGA) Technique for the Study of the Regulation of Photosynthetic Responses.
Keywords: Plant science; Botany; Plant biochemistry; Plant Sciences; Plant Biochemistry